2017
DOI: 10.1177/0973801016676013
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics and Total Factor Productivity: Evidence from Indian Manufacturing Firms

Abstract: Measurement of the productivity of firms is an important research issue in productivity literature. Over the years, various methods have been developed to measure firm productivity across the globe. But there is no unanimity on the use of methods, and research on the identification of factors which determine productivity has been neglected. In view of these gaps, this study aims to measure total factor productivity (TFP) and tries to identify firm-specific factors which determine productivity of Indian manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…With respect to the impact of firm size and age, our empirical results demonstrated that firms >200 workers were more productive than the very small and small sizes (<200 employees), of which enterprises >300 workers were the most productive ones. These findings were in line with those of Van Biesebroeck (2005) for African economies and Satpathy et al (2017) for India but were in contrast to those of Srithanpon (2016) and Fernandes (2008) for the case of Thailand and Bangladesh, respectively. Van Biesebroeck (2005) also noted that larger firms were shown to be more productive in developed countries like the United States.…”
Section: Discussionsupporting
confidence: 87%
“…With respect to the impact of firm size and age, our empirical results demonstrated that firms >200 workers were more productive than the very small and small sizes (<200 employees), of which enterprises >300 workers were the most productive ones. These findings were in line with those of Van Biesebroeck (2005) for African economies and Satpathy et al (2017) for India but were in contrast to those of Srithanpon (2016) and Fernandes (2008) for the case of Thailand and Bangladesh, respectively. Van Biesebroeck (2005) also noted that larger firms were shown to be more productive in developed countries like the United States.…”
Section: Discussionsupporting
confidence: 87%
“…Firm size may have positive effects on firm TFP if larger firms benefit from learning‐by‐doing effects, exploit scale economies, or access capital at lower costs than smaller firms (Biesebroeck, ; Jovanovic, ; Lee & Tang, ; Malerba, ). On the other hand, there could be negative effects on TFP if large firms are not able to respond easily to the changing market environment, due to their inflexibility (Satpathy, Chatterjee, & Mahakud, ; Tornatzky & Fleischer, ; Utterback, ). As far as the effect of firm age on firm TFP, we may expect older firms to have higher TFP than younger ones, due to their accumulated learning over the past (Jensen, McGuckin, & Stiroh, ; Jovanovic & Nyarko, ); or that younger firms produce with greater efficiency than older ones because they are more capable of adapting to a changing environment.…”
Section: Econometric Model and Methodologymentioning
confidence: 99%
“…Previous studies have used different factors such as gross value added and output as a dependent variable to assess the performance, technical efficiency (TE), and determinants of firms in the Indian manufacturing sector (Rajesh, 2007;Mazumdar, Rajeev & Ray, 2009;Kumar & Arora, 2012;Pattnayak & Chadha, 2013;Sahu, 2015;Mitra, Sharma & Véganzonès-Varoudakis, 2016;Kapoor, 2016;Sen & Das, 2016;Chaudhuri, 2016;Satpathy, Chatterjee & Mahakud, 2017;Kumar & Paul, 2019;Chawla & Manrai, 2019;Singh, Ashraf & Arya, 2019). The summary of the most relevant studies is given in Table 3.…”
Section: Selection Of Dependent and Independent Variablesmentioning
confidence: 99%